Research extension farmer linkages in Lao PDR : (SEAMEO SEARCA, 2001)
This report recommends immediate courses of action in strengthening Research Extension farmer linkages. This makes delivery and adoption of relevant and improved agricultural technologies for increased productivity and profitability, through innovative Research Extension Farmer linkages, critical to achieving the MDGs.